2009
DOI: 10.1007/s11524-009-9403-2
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Retrospective Geocoding in Population Studies: The Jackson Heart Study

Abstract: The increasing use of geographic information systems (GIS) in epidemiological population studies requires careful attention to the methods employed in accomplishing geocoding and creating a GIS. Studies have provided limited details,hampering the ability to assess validity of spatial data. The purpose of this paper is to describe the multiphase geocoding methods used to retrospectively create a GIS in the Jackson Heart Study (JHS). We used baseline data from 5,302 participants enrolled in the JHS between 2000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 25 publications
0
34
0
Order By: Relevance
“…The study population included adults aged 21–85 from three counties in the Jackson Metropolitan Area—Hinds, Madison, and Rankin— and was obtained using four sampling strategies: a random sample of adults drawn from a commercially available list of households with adults aged 35–84 (17%); volunteers aged 35–84 recruited through participant referral or outreach activities (30%); participants in the Jackson field center of the Atherosclerosis Risk in Communities (ARIC) study (31%); and relatives of JHS participants, ≥ 21 years of age comprising the JHS Family Sub-Study (22%). A total baseline sample of 5,301 participants (men, n=1,906; women, n=3,395) were recruited into the JHS and 98.8% (n=5,236) were retrospectively geocoded to 102 census tracts (Robinson et al, 2010). Hickson et al (2011) conducted a spatial Bayesian analysis of the JHS which showed that at the census tract level, the sample was representative of the underlying African American population living within the Jackson Metropolitan Area with two exceptions: the distribution of JHS women was more representative than JHS men, and participants residing in mixed and predominantly African American census tracts were more representative than those residing in predominantly white census tracts.…”
Section: Methodsmentioning
confidence: 99%
“…The study population included adults aged 21–85 from three counties in the Jackson Metropolitan Area—Hinds, Madison, and Rankin— and was obtained using four sampling strategies: a random sample of adults drawn from a commercially available list of households with adults aged 35–84 (17%); volunteers aged 35–84 recruited through participant referral or outreach activities (30%); participants in the Jackson field center of the Atherosclerosis Risk in Communities (ARIC) study (31%); and relatives of JHS participants, ≥ 21 years of age comprising the JHS Family Sub-Study (22%). A total baseline sample of 5,301 participants (men, n=1,906; women, n=3,395) were recruited into the JHS and 98.8% (n=5,236) were retrospectively geocoded to 102 census tracts (Robinson et al, 2010). Hickson et al (2011) conducted a spatial Bayesian analysis of the JHS which showed that at the census tract level, the sample was representative of the underlying African American population living within the Jackson Metropolitan Area with two exceptions: the distribution of JHS women was more representative than JHS men, and participants residing in mixed and predominantly African American census tracts were more representative than those residing in predominantly white census tracts.…”
Section: Methodsmentioning
confidence: 99%
“…The study population included adults aged 21-85 residing in the Jackson Metropolitan area and was obtained using four sampling approaches: a random sample of adults drawn from a commercially available list of households with adults aged 35-84 (17%); volunteers aged 35-84 recruited through participant referral or outreach activities (30%); participants in the Jackson field center of the Atherosclerosis Risk in Communities (ARIC) study (31%); and relatives of JHS participants, ≥21 years of age comprising the JHS Family Sub-Study (22%). A total of 5,301 participants were recruited into the JHS of whom 99% were retrospectively geocoded to 102 census tracts (32). …”
Section: Methodsmentioning
confidence: 99%
“…Each participant’s residential mailing address was geocoded to the census tract and used as a proxy for neighborhood. 25 Neighborhood SEP was defined as the median household income from 2000 US Census. Neighborhood SEP was divided into tertiles: ≤$25,900 (33.6%), $26,000–$35,000 (32.9%), and >$35,000 (33.6) and also examined continuously in s.d.…”
Section: Methodsmentioning
confidence: 99%